Ministry of Agriculture, Forestry and Fisheries - (:unkn) unknown (My University, 2011)
Vision To be innovative when we facilitate and stimulate the efficient utilisation of resources within the sector, and to adopt a holistic approach to agriculture and rural development. Mission To create the enabling environment for the entrepreneurial drive of farmers, fisher-folk and other related target groups to strive to increase agri-food production, processing, marketing; thus increasing employment, rural income, food security and foreign exchange earnings, while ensuring the efficient utilisation and sustainability of the Nation's natural resources.
Keywords: Agriculture, Forestry and Fisheries